Foundation models as infringers: should large-scale AI training trigger collective licensing obligations under EU law? - Lajovic, Tomaž (knjige, 2025)
The essay by Tomaž Lajovic addresses the copyright implications of foundation models (FMs), particularly large language models, under EU law. It examines how training datasets, memorisation, and output generation implicate copyright and database rights, and assesses whether collective licensing regimes or exemptions with remuneration rights could balance the interests of AI developers and rightsholders.
Keywords: Avtorske pravice; avtorsko pravo; baze podatkov; elektronske knjige; Umetna inteligenca